Anti-tuberculosis activity research of 5-(thiophen-2-ylmethyl)- 4H-1,2,4-triazole-3-thiol - Safonov, A. A.; Zazharskyi, V. V.; Сафонов, Андрій Андрійович; Зажарський, В. В.; Сафонов, А. А.; Зажарский, В. В. (Запорізький державний медичний університет, 2019)
Introduction. 1,2,4-Triazole derivatives have already proven themselves to be compounds with low toxicity and high antimicrobial, antifungal, antiviral, hepatoprotective activity. The aim of work is to research the anti-tuberculosis activity of 5-(thiophen-2-ylmethyl)-4H-1,2,4-triazoles-3-thiol on the bacteria strain M. bovis. Materials and methods. At the beginning of the experiment, the effect of the drug concentration and the pH of the medium on the growth rate of the culture at 37 °C was detected. M. bovis 100 passage was selected for this purpose, which was cultured at 37 °C with 5-(thiophen- 2-ylmethyl)-4H-1,2,4-triazole-3-thiol at the indicated concentrations in a thermostat for 3 months on medium with pH 6.5 (ten test tubes with each medicine concentration) and pH 7.1 (ten test tubes with each medicine concentration). M. bovis 100 passage was used as a control without the addition of 5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol to the medium. Results. The results of the experiment show that the effect of the drug at different concentrations on the medium with a pH 6.5 same with pH 7.1. Growth of pathogenic strain M. bovis 100 passages throughout the observation period (90 days) have been absence for all of the test (0.1 %, 0.5 % and 1.0 %) concentrations of 5-(thiophen-2-ylmethyl)-4H-1,2,4-triazoles-3-thiol. Conclusion. It can be concluded that 0.1 %, 0.5 % and 1.0 % concentration of 5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol influence on the culture properties pathogenic strain M. bovis, which cultured on the medium with pH 6.5 and pH 7.1 at 37 °C, while holding back growth, having a tuberculostatic effect. Одна з основних проблем у сучасній оперативній і терапевтичній медицині та фармації – захворювання, що спричинені мікробними інфекціями. Похідні 1,2,4-тріазолів зарекомендували себе як сполуки з низькою токсичністю та високою протимікробною, протигрибковою, противірусною, гепатопротекторною активністю. Мета роботи – дослідження протитуберкульозної активності 5-(тіофен-2-ілметил)-4H-1,2,4-тріазол-3-тіолу щодо бактерії штаму M. bovis. Матеріали та методи. На початку досліду виявили вплив концентрації препарату та рН середовища на інтенсивність росту культури за температури 37 °С. Для цього відібрали M. bovis 100 пасажу, який культивували за температури 37 °С із 5-(тіофен-2-ілметил)-4H-1,2,4-тріазол-3-тіолом у зазначених концентраціях у термостаті протягом 3 місяців на середовищі з рН 6,5 (10 пробірок із кожною концентрацією препарату) та рН 7,1 (10 пробірок із кожною концентрацією препарату). Як контроль використали M. bovis 100 пасажу без додавання до середовища 5-(тіофен-2-ілметил)-4H-1,2,4-тріазол-3-тіолу. Результати. 0,1 %, 0,5 % та 1,0 % концентрації 5-(тіофен-2-ілметил)-4H-1,2,4-тріазол-3-тіолу активно впливають на культуральні властивості патогенного штаму M. bovis, що культивований на середовищі з рН 6,5 та рН 7,1 при температурі 37 °C, стримуючи ріст і розвиток, володіючи туберкулостатичною дією. Одной из основных проблем в современной оперативной и терапевтической медицине и фармации являются заболевания, вызванные микробными инфекциями. Производные 1,2,4-триазола зарекомендовали себя как соединения с низкой токсичностью и высоким противомикробным, противогрибковым, противовирусным, гепатопротекторным действием. Цель работы – исследование противотуберкулезной активности 5-(тиофен-2-илметил)-4H-1,2,4-триазол-3-тиола на бактерии штамма M. bovis. Материалы и методы. В начале опыта исследовали влияние концентрации препарата и рН среды на интенсивность роста культуры при температуре 37 °С. Для этого отбирали M. bovis 100 пассажа, который культивировали при температуре 37 °С с 5-(тиофен-2-илметил)-4H-1,2,4-триазол-3-тиолом в указанных концентрациях в термостате в течение 3 месяцев в среде с рН 6,5 (10 пробирок с каждой концентрацией препарата) и рН 7,1 (10 пробирок с каждой концентрацией препарата). В качестве контроля использовали M. bovis 100 пассажа без добавления к среде 5-(тиофен-2-илметил)-4H-1,2,4-триазол-3-тиола. Результаты. Таким образом, 0,1 %, 0,5 % и 1,0 % концентрации 5-(тиофен-2-илметил)-4H-1,2,4-триазол-3-тиола активно влияют на культуральные свойства патогенного штамма M. bovis, культивируемого на среде с рН 6,5 и рН 7,1 при температуре 37 °C, сдерживая рост и развитие, обладая туберкулостатических действием.
Дослідження протитуберкульозної активності 5-(тіофен-2-ілметил)-4H-1,2,4-тріазол-3-тіолу
Исследование противотуберкулезной активности 5-(тиофен-2-илметил)-4H-1,2,4-триазол-3-тиола
Keywords: 1,2,4-triazole; anti-tuberculosis activity; heterocyclic compounds; 1,2,4-тріазол; протитуберкульозна активність; гетероциклічні сполуки; 1,2,4-триазол; противотуберкулезная активность; гетероциклические соединения